The Influence of Celebrity Endorsement, Green Brand Image and Green Product Quality on Decisions to use Sharia Banking Product - Putro, Dimas Handoyo; Nurwahidin, Nurwahidin; Saratian, Eko Tama Putra (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to analyze the influence of Celebrity Endorsement, Green Brand Image, and Green Product Quality on Decisions to Use Sharia Banking Products. The population in this study who had used sharia banking products. Sampling used Non-Probability sampling with Purposive Sampling technique, with a sample size of 120 respondents. The data analysis method in this research uses the Partial Least Square (Smart-PLS) program version 3.0. The research results prove that (1) Celebrity Endorsement has a positive and significant effect on Using Decisions, (2) Green Brand Image has a positive and significant effect on Using Decisions, and (3) Green Product Quality has a positive and significant effect on Using Decisions.